UNKNOWN РAGES OF THE LIFE AND CREATIVE WAY OF THE POET-MELETIUS KICHURA - Kasian, L. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper collected, systematized and generalized information about the life and work of M.Kichura’s. Main results are archival documents, manuscripts stored in personal funds P.Arsenych, I.Romanyuk in the Department of Manuscripts of the Institute of Literature T.Shevchenko National Academy of Sciences of Ukraine.